The Beginning of a New Era in Leather and Footwear in Uzbekistan (Texas Journal of Philology, Culture and History, 2022)
A new package of privileges has been announced in the field of leather and footwear. In 2022, the leather industry is being supported. In the neighborhoods, measures are being taken to slaughter livestock and launch small mobile services for skin harvesting